THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR DEVELOPING MANAGERIAL COMPETENCE OF STUDENTS IN HIGHER EDUCATION - L.R.Djurakulova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The development of managerial competence among students in higher education has become a critical priority in the context of globalization and the increasing complexity of professional environments. This article explores the theoretical and methodological foundations underlying the formation of managerial competence in university students. Using a mixed-methods approach, the study identifies key components, pedagogical conditions, and effective strategies for fostering managerial skills. The findings demonstrate that integrating competency-based, student-centered, and practice-oriented approaches significantly enhances students’ managerial readiness. The study contributes to the theoretical understanding and offers practical recommendations for improving higher education curricula.